Melanin-concentrating hormone depresses L-, N-, and P/Q-type voltage-dependent calcium channels in rat lateral hypothalamic neurons - Gao, Xiao-Bing (Blackwell Science Inc, 2002)
Melanin-concentrating hormone (MCH), a cyclic 19-amino-acid peptide, is synthesized exclusively by neurons in the lateral hypothalamic (LH) area. It is involved in a number of brain functions and recently has raised interest because of its role in energy homeostasis. MCH axons and receptors are found throughout the brain. Previous reports set the foundation for understanding the cellular actions of MCH by using non-neuronal cells transfected with the MCH receptor gene; these cells exhibited an increase in cytoplasmic calcium in response to MCH, suggesting an excitatory action for the peptide. In the study presented here, we have used whole-cell recording in 117 neurons from LH cultures and brain slices to examine the actions of MCH. MCH decreased the amplitude of voltage-dependent calcium currents in almost all tested neurons. The inhibition desensitized rapidly (18 s to half maximum at 100 nm concentration) and was dose-dependent (IC(50) = 7.8 nm) when activated with a pulse from –80 mV to 0 mV. A priori activation of G-proteins with GTPγS completely eliminated the MCH-induced effect at low MCH concentrations and reduced the MCH-induced effect at high MCH concentrations. Inhibition of G-proteins with pertussis toxin (PTX) blocked the MCH-induced inhibitory effect at high MCH concentrations. Pre-pulse depolarization resulted in an attenuation of the MCH-induced inhibition of calcium currents in most neurons. These data suggest that MCH exerts an inhibitory effect on calcium currents via PTX-sensitive G-protein pathways, probably the G(i)/G(o) pathway, in LH neurons. L-, N- and P/Q-type calcium channels were identified in LH neurons, with L- and N-type channels accounting for most of the voltage-activated current (about 40 % each); MCH attenuated each of the three types (mean 50 % depression), with the greatest inhibition found for N-type currents. In contrast to previous data on non-neuronal cells showing an MHC-evoked increase in calcium, our data suggest that the reverse occurs in LH neurons. The attenuation of calcium currents is consistent with an inhibitory action for the peptide in neurons.